The incidence of varicella and herpes zoster in Massachusetts as measured by the Behavioral Risk Factor Surveillance System (BRFSS) during a period of increasing varicella vaccine coverage, 1998-2003 - Clements Karen M; Zhang Zi; Jumaan Aisha O; Lett Susan M; Brooks Daniel R; Yih W; Seward Jane F (BMC, 2005)
Abstract Background The authors sought to monitor the impact of widespread varicella vaccination on the epidemiology of varicella and herpes zoster. While varicella incidence would be expected to decrease, mathematical models predict an initial increase in herpes zoster incidence if re-exposure to varicella protects against reactivation of the varicella zoster virus. Methods In 1998-2003, as varicella vaccine uptake increased, incidence of varicella and herpes zoster in Massachusetts was monitored using the random-digit-dial Behavioral Risk Factor Surveillance System. Results Between 1998 and 2003, varicella incidence declined from 16.5/1,000 to 3.5/1,000 (79%) overall with ≥66% decreases for all age groups except adults (27% decrease). Age-standardized estimates of overall herpes zoster occurrence increased from 2.77/1,000 to 5.25/1,000 (90%) in the period 1999-2003, and the trend in both crude and adjusted rates was highly significant (p < 0.001). Annual age-specific rates were somewhat unstable, but all increased, and the trend was significant for the 25-44 year and 65+ year age groups. Conclusion As varicella vaccine coverage in children increased, the incidence of varicella decreased and the occurrence of herpes zoster increased. If the observed increase in herpes zoster incidence is real, widespread vaccination of children is only one of several possible explanations. Further studies are needed to understand secular trends in herpes zoster before and after use of varicella vaccine in the United States and other countries.